PENERAPAN LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK MODELLING UNTUK MENINGKATKAN ETIKA PERGAULAN SISWA DI SMP MA’ARIF 4 PAMEKASAN - Ayu, Anita Tiara; Sa’idah, Ishlakhatus (LPPM STKIP PGRI Bandar Lampung, 2020)
In the millennial era like today, it is very important to apply good social ethics, especially for grade VII students. This is because VII grade students are in a transition period from elementary school level to the junior high school level. At that time, students who have just adapted can still be said to be unstable in their behaviour due to the influence of the social flow. Therefore, this study aims to identify and describe the use of group guidance services with modelling techniques to improve student social ethics. Based on this, there are main problems that become the main studies in this research, namely: first, to find out the picture of the social ethics of SMP Ma'arif 4 Pamekasan students, second, to find out the application of group guidance with modelling techniques to improve the social ethics of student Junior High School Ma’arif 4 Pamekasan. This research is included in the Guidance and Counseling Action Research. Researchers carry out the research directly by providing group guidance services with modelling techniques to students which aim to improve students' social ethics. Sources of data were obtained through the results of questionnaires, observations, interviews, and documentation. The informants in this study were counselling teachers and class VII A homeroom teachers. The results of this study indicate that: first, the social ethics of class VII A students at Junior High School Ma'arif 4 Pamekasan is still low. This was explained by the counselling teacher and homeroom teacher of class VII A when the researcher conducted the interview. Second, the application of group guidance services with effective modelling techniques to improve the social ethics of class VII A students of Junior High School Ma'arif 4 Pamekasan. This is evidenced by the results of the pre-cycle questionnaire with an average value of 61.27% which increased in the first cycle with an average value of 72.13% and also increased in the second cycle with an average value of 88.39%.